BIOCHEMICAL CHANGES IN THE STORED WHOLE BLOOD ASSESSED AT PERIODIC INTERVALS IN CPDA-1 ANTICOAGULANT CONTAINING BLOOD BAGS: A STUDY AT THE BLOOD BANK OF TERTIARY CARE HOSPITAL OF SOUTHERN RAJASTHAN - REWAL, DIKSHA; SHARMA, RAJARAM; LODHA, SAMBHAV; PRAKASH, SANJAY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were to study the various biochemical changes occurring in a stored whole blood unit at day 0, day 17th, and the 35th day in full blood bag containing citrate phosphate dextrose adenine-1 anticoagulant. Methods: A cross-sectional descriptive study had been carried out among 110 healthy volunteer donors in the Department of Transfusion Medicine, RNT Medical College, Udaipur, between August 2019 and July 2020. A 10 mL blood sample from each bag containing anti-coagulated blood being collected, and the level of sodium, potassium, chloride, total protein, and albumin were measured on days 0, 17th, and the 35th. Mean and standard deviation had been calculated for the parameters, a one-way analysis of variance test was applied to compare the differences, and a p<0.05 was considered statistically significant. Results: A higher proportion of males in the age group 18–27 years, and a generally steady increase in serum potassium level with a steady decrease in serum sodium, chloride, total protein, and albumin levels over the 35-day storage period. Conclusions: In this study, stored whole blood undergoing changes in its biochemical parameters had been studied and found to be significant. The study also recommends transfusion of fresh blood for high-risk patients.